Herpesviruses (Henry Stewart Talks, 2025)
Herpesvirus structure and classification, Life-long latency and biphasic cycle, Modes of transmission, Clinical symptoms and presentations, Diagnostic and treatment strategies, Prevention and vaccine development, Challenges in herpesvirus management